Gossypiboma: Retained Surgical Sponge after a Gynecologic Procedure - Aziz Sümer; M. Ali Çarparlar; Ömer Uslukaya; Vedat Bayrak; Çetin Kotan; Ozgur Kemik; Umit Iliklerden (Case Reports in Medicine)
We report on a case of gossypiboma. A 54-year-old woman was admitted to our hospital with abdominal mass. She had undergone a caesarean operation 23 years previously. The mass in the right abdominal quadrant was suspected by abdominal computed tomography and magnetic resonance imaging. The mass was removed by laparotomy excision and the final diagnosis was gossypiboma.